University Enrollment and Graduate Trends: Basis for Long-Term Development Plan - S. Guiamalon, Tarhata; Amad, Amerhussien; Dalamban, Fatima (South Asian Journal of Social Sciences and Humanities, 2025)
Data on university enrollment and graduates helps determine the demand and effectiveness of programs offered. It will serve as a basis for planning, resource allocation, and strategic development. The study examined the enrollment and graduation trends at Cotabato State University. In particular, the enrollment and graduation trends of Cotabato State University for Academic Years 2018-2019 to 2024–2025, according to levels. The study employed a descriptive research method and documentary analysis. The study reveals that the total enrollment decreased from AY 2018-2019 to AY 2019-2020, following the same pattern as undergraduate enrollment. From 15,085 students in AY 2022-2023 to 21,224 students in AY 2023-2024, enrollment increased significantly. As of AY 2024-2025, the number of students enrolled is the highest, at 24,835. The enrollment trend initially declined, particularly in AY 2019-2020, with a significant 17.8% decrease compared to AY 2018-2019. In the following years, however, there were fluctuations, with AY 2020-2021 reporting an increase of 15.0%, AY 2022-2023 reporting an increase of 9.1%, and AY 2021-2022 reporting a decrease of 11.2%. In addition, during AY 2023-2024, there was a substantial increase of 40.7%. Furthermore, in AY 2024-2025, there was also a 17.0% increase compared to AY 2023-2024. The number of undergraduate graduates shows more fluctuations, with a significant decrease between AY 2018-2019 and AY 2019-2020 from 1,862 to 1,097. Between AY 2019-2020 and AY 2022-2023, the numbers remain relatively stable, with significant increases in AY 2023- 2024 and AY 2024-2025. Overall, the number of graduates increased from 2,034 in AY 2018- 2019 to 2,634 in AY 2024-2025. As the years progressed, there was a gradual increase in AY 2019-2020, followed by a significant decrease in AY 2019-2020. According to these data, the graduate program appears to be growing, especially in AY 2023-2024. The undergraduate program has fluctuated but shown an increase in AY 2024-2025 compared to AY 2018-2019. AY 2019-2020 saw a significant decrease of 31.12%. There are also decreases in the following two years (AY 2020-2021 and AY 2021-2022), although at a slower pace. There was a slight increase in AY 2022-2023, followed by significant increases in AY 2023-2024 (36.62%) and AY 2024-2025 (43.23%). As a result of these data, it can be said that graduation rates dropped significantly at first, but then showed a strong rebound in the later years. It indicates a potential shift in trends or successful initiatives in AY 2023-2024 and AY 2024-2025.